Kualitas Butir Soal Ujian Akhir Semester II Mata Pelajaran Matematika - Anita Amelia Ole; Ellen Elisyabeth. Lado Djo (Journal on Education, 2022)
After learning is complete, students are required to take a test to see their ability of students after participating in learning. Anita, Tyowati, and Zuldafrial (2018) said that test questions (instruments) are a tool that can be used by teachers to assess how much material is absorbed in teaching and learning activities. This descriptive quantitative research aims to find out the quality of the second-semester final exam questions in mathematics that are tested through two aspects, namely reliability, and level of difficulty. The instruments used were questions that had been prepared by the mathematics teacher and answer sheets from 31 student respondents. The results of this study showed that the second-semester test questions in mathematics had high reliability. The difficulty level of the multiple choice questions that were too easy = 2 items, medium = 25 items, and too difficult = 2 items, and the difficulty level of the filled-in forms that were moderate = 3 items, too difficult = 1 item. From the results of this study, it is hoped that the teacher will re-analyze the quality of the items through aspects of difficulty level that do not meet the quality standards of the items